PENGENALAN BANTUAN HIDUP DASAR (BHD) PADA MASYARAKAT TJ. PENGAPIT KOTA BATAM TAHUN 2025 - Ditte Ayu Suntara; Afif D Alba, Dedi Fatrida, Nadya Ulfa Kesumawardani, Trisya Yona Febrina, Dedy Siska, T. Eltrikanawati, Didi Yunaspi, Mawardi Badar, Made Tantra Wirakesuma, Fasida Dharma Yudastoro, Dessy (JOURNAL OF COMMUNITY DEDICATION, 2025)
Basic life support (BLS) is an action taken to increase the chances of survival for cardiac arrest victims. The general public can perform BLS with basic information and knowledge, because the success of BLS actions is influenced by knowledge and attitudes about BLS. Basic life support (BLS) is an action taken to increase the chances of survival for cardiac arrest victims. The success of BLS actions is influenced by knowledge and attitudes about BLS. This Community Service Activity was carried out in Tanjung Pengapit, Batam City in May 2025, the target of this Community Service activity was all residents in Tanjung Pengapit, Batam City. The results obtained were the level of knowledge of residents in the lecture and simulation education group before being given BLS education, namely that most were in the sufficient category as many as 19 respondents (63%). While a small part was in the good category as many as 11 respondents (37%). After being given BLS education and simulation, data was obtained on the level of student knowledge, most of which were in the sufficient category, 26 respondents (87%). Meanwhile, a small part was in the poor category, 4 respondents (13%).